1997
DOI: 10.1007/s005850050573
|View full text |Cite
|
Sign up to set email alerts
|

The sunspot cycle, the QBO, and the total ozone over Northeastern Europe: a connection through the dynamics of stratospheric circulation

Abstract: Abstract. The interaction between the factors of the quasi-biennial oscillation (QBO) and the 11-year solar cycle is considered as an separate factor in¯uencing the interannual January±March variations of total ozone over Northeastern Europe. Linear correlation analysis and the running correlation method are used to examine possible connections between ozone and solar activity at simultaneous moment the QBO phase. Statistically signi®cant correlations between the variations of total ozone in February and, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Combining our results with those of Labitzke and Van Loon (1988, Soukharev (1997Soukharev ( , 1999 and Varotsos (1989) concerning ozone content and temperature in the Northern Polar stratosphere, it could be said that during maximum solar activity, higher geomagnetic activity and UV levels coincide with the easterly phase of the QBO together with lower temperatures and less ozone in the Northern Polar cap, while the westerly phase coincide with lower geomagnetic activity and UV levels together with stratospheric warming and more ozone in the Northern Polar cap. During minimum solar activity levels this relationship is reversed.…”
Section: Article In Presssupporting
confidence: 58%
“…Combining our results with those of Labitzke and Van Loon (1988, Soukharev (1997Soukharev ( , 1999 and Varotsos (1989) concerning ozone content and temperature in the Northern Polar stratosphere, it could be said that during maximum solar activity, higher geomagnetic activity and UV levels coincide with the easterly phase of the QBO together with lower temperatures and less ozone in the Northern Polar cap, while the westerly phase coincide with lower geomagnetic activity and UV levels together with stratospheric warming and more ozone in the Northern Polar cap. During minimum solar activity levels this relationship is reversed.…”
Section: Article In Presssupporting
confidence: 58%
“…Troshichev and Gabis (1998), Soukharev and Hood (2001) and Gabis and Troshichev (2004) showed that the UV irradiance undergoes quasibiennial periodicity which may have an effect on the stratospheric QBO. After this idea, Elias and Zossi de Artigas (2003) estimated the running correlation between the QBO signal in the 10.7 cm solar radio emission, F10.7, and the equatorial stratospheric QBO and found a quasi-decadal variation in the correlation coefficient series similar to what Kodera (1993), Soukharev (1997Soukharev ( , 1999 and Salby and Callaghan (2004) found.…”
Section: Introductionsupporting
confidence: 56%
“…The running correlation between the QBO and certain atmospheric and solar parameters, observed by some authors (Kodera, 1993;Soukharev, 1997Soukharev, , 1999Elias and Zossi de Artigas, 2003;Salby and Callaghan, 2004;Zossi de Artigas and Elias, 2005), present a quasi-decadal modulation. As an example, we present in this section some results using experimental time series.…”
Section: Running Correlations With Experimental Time Seriesmentioning
confidence: 96%
See 2 more Smart Citations